Survey Reveals Training Needs for Airblast Sprayer Applicators, Farm Managers, Owners and Pest Control Advisers. (1st April 2019) - Wunderlich, Lynn; Niederholzer, Franz; Blecker, Lisa; Smith, Rhonda; Strmiska, Matthew; Symmes, Emily; Bolton, Stephanie
In California, pesticide applicators and/or their supervisors routinely complete mandatory pesticide safety training; however, little training in spray application calibration or pesticide drift management is required to apply, supervise or prescribe pesticides. This is particularly problematic for maximizing efficacy of crop sprays and managing off-site movement of pesticides in the millions of acres of winegrapes and tree nuts grown in California and sprayed by air-assist (airblast) sprayers. A 2008 study by the Coalition for Urban Rural Environmental Stewardship (CURES), a California group that promotes pesticide stewardship, showed the need for sprayer calibration training. CURES measured nozzle output performance of 69 orchard sprayers pre- and post-calibration as compared to the manufacturer's specifications. After worn nozzle replacement and proper calibration, 32% of the sprayers improved their output efficiency by 5–10%, 15% of the sprayers improved by 10–20%, and 12% showed a greater than 20% efficiency increase, with a greatest net efficiency improvement of 76.3%. To address the ongoing need for spray application training, our team of University of California Agricultural and Natural Resources (UC ANR) advisors, faculty, and statewide academics along with private industry leaders are developing a training course on best practices for airblast applications. Our training will focus on sprayer calibration, spray coverage, and drift management. The target audiences are: applicators, supervisors, owners and pest control advisers (PCAs) working in winegrape and orchard cropping systems in northern California (NCA). We developed a survey to identify current practices and perceptions of the importance of spray related topics, as well as satisfaction with previous training, to inform our training program. The survey was distributed to NCA winegrape and orchard industry members. We received 219 responses from applicators, their supervisors, growers and PCAs. This report summarizes the survey's findings.